Development of Business Partner Selection - Bivainis, Juozas (Ekonomika, 2006)
The paper presents an integrative approach to business partner selection. aimed at increasing the economic validity of decision-making. The proposed model consists of the following six interrelated components: searching for partners, preliminary selection, complex assessment, negotiating with potential partners, signing of contracts, monitoring of contract implementation. Links among the components and solution of all the above tasks using the model are supported by an integrated database of partnership objects and potential as well as actual business partners. In this context assessment of business partners is considered as a multicriteria task of ranking alternatives. The similarity function of partnership objects as well as a three-level-criteria system are adapted for solving this task. A case study is conducted to illustrate the feasibility of the proposed model, and the test results confirm its suitability.